2019
DOI: 10.1016/j.omtm.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Pharmacodynamics and Pharmacokinetics of MSCs to Overcome Limitations in Their Clinical Translation

Abstract: Recently, mesenchymal stromal stem cells (MSCs) have been proposed as therapeutic agents because of their promising preclinical features and good safety profile. However, their introduction into clinical practice has been associated with a suboptimal therapeutic profile. In this review, we address the biodistribution of MSCs in preclinical studies with a focus on the current understanding of the pharmacodynamics (PD) and pharmacokinetics (PK) of MSCs as key aspects to overcome unsatisfactory clinical benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 110 publications
(264 reference statements)
2
33
0
Order By: Relevance
“…Along the same line, it has been demonstrated that infused apoptotic MSCs can act together with monocytes to promote immunosuppression in an animal model of graft versus host disease . Collectively, MSC‐based pharmacological developments are still missing robust pharmacodynamic and pharmacokinetic models to be applied in the different clinical situations . This surely calls for ad hoc investigations able to reflect the complexity of these cell types, their interactions with host cells and diseases in which they are applied.…”
Section: Why Msc Functions Do Not Solidly Shift Them Toward Clinic Yet?mentioning
confidence: 99%
“…Along the same line, it has been demonstrated that infused apoptotic MSCs can act together with monocytes to promote immunosuppression in an animal model of graft versus host disease . Collectively, MSC‐based pharmacological developments are still missing robust pharmacodynamic and pharmacokinetic models to be applied in the different clinical situations . This surely calls for ad hoc investigations able to reflect the complexity of these cell types, their interactions with host cells and diseases in which they are applied.…”
Section: Why Msc Functions Do Not Solidly Shift Them Toward Clinic Yet?mentioning
confidence: 99%
“…This can be combined with experiments that gather converging and discriminant evidence to identify mechanistic underpinnings of an intervention to increase translational validity and identify limitations and boundary conditions. For example, studies of pharmacodynamics and kinetics in preclinical models support in-depth understanding of physiological processes and allow comparison with human pharmacological processes ( Salvadori et al, 2019 ; Tuntland et al, 2014 ).…”
Section: What To Replicate and How To Replicatementioning
confidence: 99%
“…MSC systemic administration, which must follow Good Manufacturing Practice (GMP) rules, is not associated to a significant evidence of cell engraftment even in presence of clinical benefit, due to the entrapment of MSCs in the microvasculature of filter organs, such as lungs (Moll et al, 2016;Salvadori et al, 2019). Other biology aspects can interfere with therapeutic efficacy of MSCs.…”
Section: Msc-ev-based Immunotherapymentioning
confidence: 99%